Cavitating leukoencephalopathy with multiple mitochondrial dysfunction syndrome and NFU1 mutations - Invernizzi, Federica; Ardissone, Anna; Lamantea, Eleonora; Garavaglia, Barbara; Zeviani, Massimo; Farina, Laura; Ghezzi, Daniele; Moroni, Isabella (Frontiers in Genetics, 2014)
Multiple Mitochondrial Dysfunction Syndrome (MMDS) comprises a group of severe autosomal recessive diseases with onset in early infancy and characterized by a systemic disorder of energy metabolism, resulting in weakness, respiratory failure, lack of neurological development, lactic acidosis and early death . Biochemical findings include defects of complexes I, II and III of the mitochondrial respiratory chain and severe deficiency of Pyruvate dehydrogenase complex (PDHc). Three genes have been associated with MMDS since now: NFU1, BOLA3, and IBA 57. We describe an Italian male patient presenting with severe psychomotor regression after an infectious episode, lactic acidosis, hyperglycinemia, reduction of respiratory chain complex II associated with a marked deficiency of PDHc activity. He carried two heterozygous mutations in NFU1, one novel (p.C210F) and one previously reported (p.G189R) missense change affecting highly conserved residues. A severe leukoencephalopathy with cavitations in deep white matter was disclosed at brain MRI, suggesting a peculiar neuroradiological phenotype associated with defect in this gene.